XBP-1 is required for biogenesis of cellular secretory machinery of exocrine glands - Lee, Ann-Hwee (Nature Publishing Group, 2005)
The secretory function of cells relies on the capacity of the endoplasmic reticulum (ER) to fold and modify nascent polypeptides and to synthesize phospholipids for the subsequent trafficking of secretory proteins through the ER–Golgi network. We have previously demonstrated that the transcription factor XBP-1 activates the expression of certain ER chaperone genes and initiates ER biogenesis. Here, we have rescued the embryonic lethality of XBP-1 deficient fetuses by targeting an XBP-1 transgene selectively to hepatocytes (XBP-1(−/−);Liv(XBP1)). XBP-1(−/−);Liv(XBP1) mice displayed abnormalities exclusively in secretory organs such as exocrine pancreas and salivary gland that led to early postnatal lethality from impaired production of pancreatic digestive enzymes. The ER was poorly developed in pancreatic and salivary gland acinar cells, accompanied by decreased expression of ER chaperone genes. Marked apoptosis of pancreatic acinar cells was observed during embryogenesis. Thus, the absence of XBP-1 results in an imbalance between the cargo load on the ER and its capacity to handle it, leading to the activation of ER stress-mediated proapoptotic pathways. These data lead us to propose that XBP-1 is both necessary and sufficient for the full biogenesis of the secretory machinery in exocrine cells.